The Resilience of Elementary School Students Through a Project to Strengthen The Pancasila Student Profile - Krisna, I Made Krisna Dwi Payana; Putu Nanci Riastini; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2023)
Each student's resilience level influences students’ ability to implement projects to strengthen Pancasila student profiles. This research aims to describe students' resilience by implementing a project to strengthen the profile of Pancasila students in elementary schools. This research belongs to the type of quantitative descriptive research. The population in this study was 236 students of class IV SD. Sampling in the study was carried out using a proportional random sampling technique by randomly taking samples from members of the population without regard to strata so that the total sample was 148 students of class IV SD. Data collection in the study was carried out using observation, interview, and questionnaire distribution methods, with the research instrument being a student resilience questionnaire. The data obtained in the study were then analyzed using descriptive statistical analysis techniques. From the results of data analysis, it was obtained that the average value of students' resilience through the implementation of the Pancasila student profile strengthening project was 76.95. When converted to the categorization of resilience according to Stoltz, it is included in the medium category (Campers). Based on the results of this analysis, students' resilience through the implementation of Pancasila strengthening projects in elementary schools is in the medium category.